Efeito da fotobiomodulação na reação local induzida pelo veneno da serpente Bothrops alternatus em seus estágios juvenil e adulto - David, Amanda Cabral (2021)
Bothrops snakes are responsible for most snakebites in Latin America. Bothropic envenoming causes both systemic and severe local effects. Furthermore, it is described that venoms from young and adult snakes have differences in their composition, which can lead to differences in the evolution of the local picture. Bothropic antivenom is the treatment of first choice, however, its effectiveness is limited, being able to neutralize only the systemic effects. It has been shown in previous studies that photobiomodulation (PBM) is promising in reducing local effects induced by bothropic snakes. The aim of this study was to expand the knowledge of the actions of low-level laser (LLL) on the local effect, after the action of the snake venom Bothrops alternatus (VBa), in its juvenile (VBaJ) and adult (VBaA) stages. For this, in vivo experiments were carried out with Balb-C mice and, in vitro with C2C12 muscle cells. For the treatment, LLL, 660 nm, 100 mW and 40 seconds of irradiation were used. In vivo, the animals were injected with VBaJ or VBaA, or only with saline, and the groups that received PBM, the treatment was conducted 30 minutes after the injection of the venoms. After 6 hours, edema, inflammatory infiltrate, myotoxicity and histology of the gastrocnemius muscle were analyzed, and after 1, 3, 6 and 24 hours, hyperalgesia was analyzed. In vitro, C2C12 cells received either VBaJ or VBaA, or culture medium alone, and were immediately irradiated with LLL. After 3 hours of the action of the venoms, cell viability, cytotoxicity, differentiation, membrane potential, proliferation, and cellular apoptosis/necrosis were evaluated. It was observed that, in vivo, VBaJ and VBaA, at the applied doses, were able to induce edema, inflammatory infiltrate, hemorrhage, to increase hyperalgesia and to cause myotoxicity and myonecrosis, at different intensities. In vitro, the two venoms also caused cytotoxicity, decreased cell differentiation, increased cell proliferation, and also induced apoptosis. Treatment with PBM, in vivo, was effective in reducing myotoxicity, leukocyte migration and hyperalgesia caused by the two venoms tested. Furthermore, it reduced the edema caused by VBaJ. In vitro, PBM induced cell differentiation and proliferation and also reduced apoptotic and necrotic cells. It can be concluded that, although both venoms (juvenile and adult) are capable to induce local reactions, there is a difference in the magnitude of these effects, both in vivo and in vitro, and treatment with PBM was shown to be beneficial in reducing these local reactions induced by the venoms of this snake.